CONTROL OF STEEL FLOWS IN CRYSTALLIZER WITH THE HELP OF CLOSED-BOTTOM SLEEVE - D. N. Andrianov; M. N. Novikov; A. I. Stolarov (Литьë и металлургия)
The numerical modeling of the melt flowing processes in crystallizer and liquid pool of steel is carried out. The constructive decisions f or organization of the melt rotation in crystallizer are given.